Role and mechanism of IL ‐ 17 and its gene polymorphisms in dyslipidemia caused by obstructive sleep apnea syndrome in children: IL ‐ 17 in dyslipidemia by obstructive sleep apnea - Yang, Jin (Cellular and Molecular Biology, 2022)
The current research was carried out to explore the role and mechanism of IL ‐ 17 and its gene polymorphisms in dyslipidemia caused by obstructive sleep apnea syndrome in children. For this aim, a total of 86 children with obstructive sleep apnea syndrome admitted to our hospital from January 2018 to January 2020 were selected as the study subjects, and the lipid-related indexes of the children were detected by a fully automatic biochemical analyzer, and they were divided into OSAHS group (54 cases), combined dyslipidemia group (32 cases), and another 40 healthy children who underwent physical examination in our hospital during the same period were selected as the healthy group. Levels of IL-7 and AHI, FEV1 / FVC were analyzed in each group, and levels of TC, TG, and LDL-C were compared to observe different sites of IL-17, namely IL-17A (rs3748067; The loci of IL-17F (rs763780, rs2397084) were genotyped in different groups to analyze the association between IL-17 and dyslipidemia in children with OSAHS. Results showed that higher IL-7 and AHI levels and lower FEV1 / FVC levels were found in the combined dyslipidemia and OSAHS groups compared with the healthy group, and higher IL-7 and AHI levels and lower FEV1 / FVC levels were found in the combined dyslipidemia group compared with the OSAHS group (P < 0.05); TC, TG and LDL-C level expression were higher in the combined dyslipidemia and OSAHS groups compared with the healthy group, and TC, TG and LDL-C level expression were higher in the combined dyslipidemia group compared with the OSAHS group (P < 0.05). IL-17 was positively correlated with TC, TG and LDL-C. It was concluded that in the development of OSAHS, IL-7 levels are significantly expressed, at the same time OSAHS children progress dyslipidemia, which has some correlation with IL-17, and IL-17 gene polymorphism, IL-17A (rs3748067); All were significantly expressed in the IL-17F (rs763780, rs2397084) locus.